New finds of trace fossils from the Bohdalec and Kraluv Dvur Formations (late Ordovician, Barandian area, Czech Republic) - Mikulas,R. (Journal of the Czech Geological Society, 1994)
An ichnoassemblage containing the trilobite traces Cruziana and Rusophycus was known in the Polyteichus Facies of the Bohdalec Formation from one locality only and was considered exceptional. Newly, this ichnoassemblage has been found at two further localities. Coupled with new finds of Phycodes ichnosp. (div. ichnosp.), Teichichnus rectus, and Rhizocorallium ichnosp., it well-illustrates a typical Cruziana Ichnofacies developed in the Polyteichus Facies. -Author